Peran istri Sebagai Pencari Nafkah Perspektif Qirā’ah mubādalah di Desa Sukorejo Kecamatan kunir Kabupaten Lumajang - Faruq, Afiful; Bayhaki, Imam (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2023)
The phenomenon of wives as breadwinners in the family remains a topic of debate among the community, including in Sukorejo Village, Kunir District, Lumajang Regency. In traditional Islamic understanding, the husband is obligated to provide for the family, as stated in QS. An-Nisā’ verse 34. However, social reality shows a shift in roles where many wives also work to earn a living, and in some cases, their income even exceeds that of their husbands. This situation creates various social and psychological dynamics within the household, affecting family harmony and public perceptions of gender roles in family economics. This study aims to analyze the phenomenon of wives as breadwinners in Sukorejo Village and examine it through the perspective of Qirā’ah Mubādalah developed by Faqihuddin Abdul Kodir. The Qirā’ah Mubādalah approach emphasizes reciprocity and partnership between men and women in interpreting religious texts, including in the distribution of economic responsibilities within the family. Thus, the participation of wives in earning a living is not considered a violation of religious roles but rather a form of mutual cooperation and shared responsibility to achieve a harmonious, loving, and merciful (sakinah, mawaddah, wa rahmah) family life. The results of this study show that about 80% of wives in Sukorejo Village actively contribute to supporting the family’s economy due to several factors, such as limited financial conditions, the husband’s illness, or unemployment. From the Qirā’ah Mubādalah perspective, such roles are permissible as long as they are based on mutual agreement, mutual consent, and do not cause imbalance within the household. The values of mubādalah—such as commitment, cooperation, deliberation, and mutual comfort—are found to sustain household harmony despite the shifting of economic roles between husband and wife.